Evaluación de la actividad fotocatalítica de la mezcla TiO2/ZnO en la remoción de azul de metileno (2019)
In the present work of degree was carried out the elaboration of a mixture of Titanium Dioxide and Zinc Oxide by means of the technique of spin coating and reactive evaporation respectively deposits in glass as a substrate in order to evaluate the potential of this mixture as photocatalyst in the process of AM removal by heterogeneous photocatalysis. For this, four different suspensions are carried out and taking into account their results, the best one is selected, then parameters such as: the spin speed of the spin coating, the temperature and the calcination time are varied. Finally, with tests of adhesion and removal of AM, the best film to be modified with ZnO is determined.